PENGEMBANGAN MEDIA GAME ULAR TANGGA DIGITAL PADA MATERI HUKUM DASAR KIMIA : Game ular tangga digital, hukum dasar kimia - Elfiza, Dinda Rifanna; Amir, Hermansyah; Ginting, Sura Menda (ALOTROP, 2025)
This research is a research and development (R&D) that aims to produce a product in the form of a web-based digital snakes and ladders game on fundamental law in chemistry. This study aims to determine the results of feasibility reviewed by experts, student responses, and implementation results after using digital snakes and ladders game media. This research uses the ADDIE development model which includes the stages of analysis, design, development, implementation, evaluation. Response test subjects were students of SMAN 8 Bengkulu City class X-2 totaling 35 students and implementation test class X-1 totaling 35 students. The instruments used in this study include interview sheets, observation sheets, students need analysis questionnaires, validation sheets, and students response questionnaires. The results of the validation of the digital Snake and Ladder Game on fundamental law in chemistry were declared very feasible by material and media validators with an average score of 4.59 and 4.59 respectively. Students' responses to the digital Snake and Ladder Game on fundamental law in chemistry included very good criteria with an average score of 4.14. The results of the implementation of digital Snake and Ladder Game on basic chemical law material get a percentage of 82.4% which includes very good criteria. It can be concluded from the results of the study that the digital Snake and Ladder Game on fundamental law in chemistry is feasible to be applied to learning with this material.